2019
DOI: 10.1177/0269881119841562
|View full text |Cite
|
Sign up to set email alerts
|

The antidepressant effect of bone marrow mononuclear cell transplantation in chronic stress

Abstract: Background: Inflammation could be a risk factor for the development of depression and change the outcome of this common chronic-recurrent mental disorder. Aims: This study aimed to investigate if bone marrow mononuclear cell (BMMC) transplantation is effective in restoring sucrose preference in rats subjected to chronic stress (CS), if it has an anti-inflammatory effect and is able to restore damaged DNA. Methods: The effect of BMMC transplantation was studied in a controlled protocol (compared with a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
(47 reference statements)
3
4
0
Order By: Relevance
“…116 In line with these findings in a rat model of chronic stress, transplanted MSCs were shown to exert an anti-depressive effect, possibly through enhancing anti-inflammatory cytokines and lowering pro-inflammatory mediators. 117 Moreover, evidence supports the notion that such a regulatory effect of MSCs on inflammation works through the secretion of bioactive components (secretome), which mainly includes cytokines, chemokines, growth factors, and extracellular vesicles (microvesicles and exosomes) (Figure 2b). 98,118,119 Indeed, MSCs have been shown to be capable of releasing extracellular vesicles, which could exhibit comparable biological functions as entire MSCs.…”
Section: Mesenchymal Stem Cells and Msc-derived Exosomes Regulate Neu...supporting
confidence: 60%
See 1 more Smart Citation
“…116 In line with these findings in a rat model of chronic stress, transplanted MSCs were shown to exert an anti-depressive effect, possibly through enhancing anti-inflammatory cytokines and lowering pro-inflammatory mediators. 117 Moreover, evidence supports the notion that such a regulatory effect of MSCs on inflammation works through the secretion of bioactive components (secretome), which mainly includes cytokines, chemokines, growth factors, and extracellular vesicles (microvesicles and exosomes) (Figure 2b). 98,118,119 Indeed, MSCs have been shown to be capable of releasing extracellular vesicles, which could exhibit comparable biological functions as entire MSCs.…”
Section: Mesenchymal Stem Cells and Msc-derived Exosomes Regulate Neu...supporting
confidence: 60%
“…It could inhibit the chronic stress‐induced up‐regulation of proinflammatory markers (IL‐1 and HMGB‐1) in the brain 116 . In line with these findings in a rat model of chronic stress, transplanted MSCs were shown to exert an anti‐depressive effect, possibly through enhancing anti‐inflammatory cytokines and lowering pro‐inflammatory mediators 117 …”
Section: Mesenchymal Stem Cells and Msc‐derived Exosomes Regulate Neu...supporting
confidence: 56%
“…In previous studies, the effects of BMMC treatment on the pilocarpine model of epilepsy were assessed during the acute epileptogenic (Costa-Ferro et al 2010;Leal et al 2014) and chronic periods (Costa-Ferro et al 2012;Venturin et al 2011;Zanirati et al 2015), as well as in clinical investigations (DaCosta et al 2018). Recently, an antiinflammatory effect of BMMC treatment was demonstrated in the unpredictable chronic stressors experimental model (do Prado-Lima et al 2019). Systemic administration of BMMC in this epilepsy model promotes functional recovery, reduce SRS, attenuates astrocyte morphological changes and neuronal loss, increase expression of genes encoding antiinflammatory cytokines and normalize expression of genes encoding proinflammatory cytokines, when transplanted 22 days post-SE (Costa-Ferro et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have demonstrated beneficial effects in intravenous BMMC transplant models with transplant occurring between 1h and 7dpi [33][34][35]; however, no beneficial effects were obtained when transplant occurred 14 or 30 dpi [35]. Although fast therapeutic actions are key in inducing recovery, safe and beneficial effects have also been shown in dogs with chronic spinal cord injury [36,37] and rats with chronic stress [38]and depression [39].…”
Section: Discussionmentioning
confidence: 99%